Optimization of Pultrusion Process Parameters via Design of Experiments and Response Surface - Faria Neto, Antonio [UNESP]; Fernando Branco Costa, Antonio [UNESP] (Wiley, 2016)
Experimental designs were implemented to investigate the effects of mold temperature and pulling speed on the tensile strength of cylindrical cables produced by pultrusion. A two-level factorial design with a central point revealed that the linear model is not applicable for describing the influence of the process parameters on the tensile strength. Additional experiments were performed to investigate the contribution of quadratic terms. A three-level factorial design revealed that only the linear and the quadratic-linear interactions can be discarded from the complete quadratic model. In the investigated range of the parameters, the tensile strength always increases with the mold temperature and decreases with the pulling speed. Thus, cables produced at the highest temperature and the lowest speed are the most resistant. Compared with the mold temperature, the pulling speed has a minor influence on the tensile strength. Based on these findings, during periods of higher demand, the pulling speed can be increased without significant loss in tensile strength. For the cases where the tensile strength is critical, the rise in speed can be compensated by a mild increase in temperature. This way, the gain in quality, translated into cables with better resistance, highly compensates for the additional energy consumption.
Keywords: design of experiments; polymer composites; response surface methodology; tensile strength